MYTHOLOGICAL REINTERPRETATION OF PERSEPHONE AS A SYMBOL OF EMPOWERMENT IN AMANDA LOVELACE’S FLOWER CROWNS AND FEARSOME THINGS - Nuristama, Ramadhina Ulfa (SIGEH ELT : Journal of Literature and Linguistics, 2025)
This article analyses Amanda Lovelace's poetry collections Flower Crowns and Fearsome Things. This article discusses how Amanda Lovelace recodes Greek mythology empowering in particular the figure of Persephone. Also addressed in this study is the manner in which Persephone, traditionally seen as a weak goddess carried off by other gods, is portrayed as having strength, determination and the complexity of woman's nature. This study has a qualitative approach with textual analysis from a women's literary criticism perspective. The results depict Persephone as a figure of both tenderness and strength, and as one of vulnerability and independence. Through these poems, women are shown taking suffering and turning it into resilience, pushing back against male narratives and becoming more than what the pressure of society represents. The reinterpretation of myth presented in this paper can be viewed as a strong means to criticize patriarchy and draw an empowering picture of women. This study further validates that contemporary poetry not only serves as an art form, but it also serves as a contemporary social critique for identity empowerment within the contemporary era.